Digital Food Marketing: What We Know, What We Should Know - Hamadeh, Sima (British Journal of Marketing Studies, 2017)
Today’s adolescents are growing up at the center of an exploding digital media culture and are primary targets for digital food marketing. A combination of factors has made them particularly valuable to interactive marketers, including their role as ‘‘early adopters’’ of new media practices and their steadily rising spending power. A trend has been observed towards increasing investment in food marketing on new media such as the Internet, social media and video games. The aim is to engage youth in emotional, entertaining experiences and to encourage them to share these experiences with their environments. There is unequivocal evidence that marketing of unhealthy food influences youth health. Therefore, there is a need: 1) to address the growing health threat facing youth in the digital marketplace, 2) to design new smart technologies to support credible nutrition communication and e-health. A formative exploratory study in Lebanon, based on social marketing approach, showed that food marketing and nutrition communication influence the knowledge, food preferences and dietary patterns of youth. Comprehensive nutrition communication on multiple media increases the power of persuasive messages that encourage healthy lifestyles. Research on digital food marketing impact on health remains underdeveloped and should be of concern to policy makers.